Pertanggungjawaban Pidana terhadap Pelaku Tindak Pidana Penggelapan Iuran Dana Badan Penyelenggara Jaminan Sosial Ketenagakerjaan - Didik Miraharja (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine how the criminal responsibility for the perpetrators of the crime of embezzling funds from the Social Security Administering Body. The type of research used is normative legal research with a statutory approach, which is supported by data obtained from library data including books, laws and regulations, and court decisions, and in this case the data is processed using qualitative analysis. Based on the results of the study that the application of elements of the criminal act of embezzlement of BPJS Employment fund contributions which is carried out continuously is regulated in Article 374 Jo. Article 64 (1) of the Criminal Code whose elements contain elements of "Whoever" and elements of "Intentionally unlawfully possessing goods that are wholly or partly owned by others but which are in their power not because of a crime due to an employment relationship or because of a search or because of obtaining wages for it. Provisions for sanctions against criminal acts of embezzlement of BPJS Employment fund contributions which are carried out continuously where the sanctions for perpetrators are prosecuted with imprisonment for 1 year and 6 months, but with various considerations from the panel of judges, where the Judge has imposed a prison sentence of 2 (two) years, although the criminal sanctions imposed by the judge are heavier than the demands of the public prosecutor.